2011
DOI: 10.1128/jvi.02087-10
|View full text |Cite
|
Sign up to set email alerts
|

The Presence of a vpu Gene and the Lack of Nef-Mediated Downmodulation of T Cell Receptor-CD3 Are Not Always Linked in Primate Lentiviruses

Abstract: Nef is an accessory protein critical for the ability of human and simian immunodeficiency viruses (HIV and SIV) to replicate efficiently in their respective hosts. Previous analyses of members of 15 different primate lentivirus lineages revealed a link between Nef function and the presence of a vpu gene. In particular, Nef proteins of all vpu-containing viruses had lost their ability to downmodulate the T cell (TCR-CD3) receptor. Here we examined Nef proteins from eight additional SIV lineages, including SIVgo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
42
0

Year Published

2011
2011
2020
2020

Publication Types

Select...
5
2

Relationship

3
4

Authors

Journals

citations
Cited by 29 publications
(46 citation statements)
references
References 63 publications
(121 reference statements)
3
42
0
Order By: Relevance
“…To examine the susceptibility of different T cell subsets to HIV-1 infection, PBMCs and HLACs were exposed to R5-and X4-tropic HIV-1 IRES-eGFP constructs containing various nef genes. It has been previously shown that these HIV-1 reporter constructs replicate efficiently in infected PBMC cultures (19,21). We found that HIV-1 infected (eGFP-positive [eGFP ϩ ]) cells were readily detectable at 3 days postinfection (Fig.…”
Section: Generation Of Hiv-1 Constructs Differing In the Tcr-cd3mentioning
confidence: 61%
See 3 more Smart Citations
“…To examine the susceptibility of different T cell subsets to HIV-1 infection, PBMCs and HLACs were exposed to R5-and X4-tropic HIV-1 IRES-eGFP constructs containing various nef genes. It has been previously shown that these HIV-1 reporter constructs replicate efficiently in infected PBMC cultures (19,21). We found that HIV-1 infected (eGFP-positive [eGFP ϩ ]) cells were readily detectable at 3 days postinfection (Fig.…”
Section: Generation Of Hiv-1 Constructs Differing In the Tcr-cd3mentioning
confidence: 61%
“…Indeed, some Nef functions may help these viruses to replicate efficiently in their natural simian hosts without causing disease (14,16). Specifically, most Nef proteins block the responsiveness of virally infected T cells to stimulation by downmodulation of T cell receptor (TCR)-CD3 from the cell surface (11,(17)(18)(19). Exceptions are Nefs of HIV-1 and its vpu-containing SIV counterparts that lack this function entirely (11,19).…”
Section: P Rimate Lentiviruses Manipulate Infected Cd4mentioning
confidence: 99%
See 2 more Smart Citations
“…HIV-1, SIVcpz, SIVgor, SIVgsn, SIVmus, SIVmon (Schindler et al, 2006). Exceptions to this association has been demonstrated since in SIVden strain, in which Nef retains the ability to downmodulate TCR/CD3, the vpu gene is present, whereas in SIVolc, which does not contain Vpu, Nef protein is unable to perform this function (Schmokel et al, 2011). Besides the role of Nef in TCR/CD3 downmodulation a question remains to be understood: does CD3 downregulation contribute to the nonpathogenic phenotype of natural SIV infections?…”
mentioning
confidence: 99%